2019
DOI: 10.1002/advs.201900719
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Complex Carbon and Metal/Carbon Systems by Secondary Electron Hyperspectral Imaging

Abstract: Carbon and carbon/metal systems with a multitude of functionalities are ubiquitous in new technologies but understanding on the nanoscale remains elusive due to their affinity for interaction with their environment and limitations in available characterization techniques. This paper introduces a spectroscopic technique and demonstrates its capacity to reveal chemical variations of carbon. The effectiveness of this approach is validated experimentally through spatially averaging spectroscopic techniques and usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…[ 9 ] As SEHI is carried out in the SEM, local variation in chemical changes and sample topography can be assessed in one step. [ 10 ] To do this, SEHI constructs a series of images of the sample area, where each image is formed from a selected SE energy band. While innovative synchronized structural and chemical characterization of materials by SEHI has many uses, this study focuses on revealing and mapping the spatial variation of functional groups that are affected by Ar plasma treatment through identifying specific energy bands for CH, OH, and CO groups.…”
Section: Figurementioning
confidence: 99%
“…[ 9 ] As SEHI is carried out in the SEM, local variation in chemical changes and sample topography can be assessed in one step. [ 10 ] To do this, SEHI constructs a series of images of the sample area, where each image is formed from a selected SE energy band. While innovative synchronized structural and chemical characterization of materials by SEHI has many uses, this study focuses on revealing and mapping the spatial variation of functional groups that are affected by Ar plasma treatment through identifying specific energy bands for CH, OH, and CO groups.…”
Section: Figurementioning
confidence: 99%
“…Therefore, the absence of this peak in the observed results is a strong indication of the successful process of crosslinking and shows that polymerization is complete. Abrams et al [23] have shown by the results of an electron beam contamination study that amorphous contamination (hydrogenated carbon) deposits on carbon-based samples can be identified through energy peaks within the 3.3-4.7 eV range. PGS-M photocured polymers show an increase of CH vibrations, specifically CH alkyl, which is associated with the cross-linking of PGS-M after photo-polymerization.…”
Section: Doi: 101002/marc201900484mentioning
confidence: 99%
“…Expected SE emission differences between the two SES plots appear in the peak intensities previously identified as sp 2 and sp 3 carbon bonding [ 27 , 30 , 35 ]. This initial baseline SES collected is useful not only to monitor carbon, but also to understand the cleanliness of an SEM chamber and what forms of contaminant are present.…”
Section: Resultsmentioning
confidence: 99%
“…This initial baseline SES collected is useful not only to monitor carbon, but also to understand the cleanliness of an SEM chamber and what forms of contaminant are present. As previous studies have shown, emission in the sp 2 energy range, an amorphous carbon contamination (ACC) region in HOPG, is an indication of EBID related contamination found within the SEM chamber [ 30 , 36 ]. Surface contamination forms will be influenced and characterised by the different chamber environments that occur in the two microscopes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation